Functional Analysis of the 3ʹ Untranslated Region of the Human GRIN1 Gene in Regulating Gene Expression in vitro - Liu Y (Dove Medical Press, 2020)
Yong-ping Liu, Xue Wu, Jing-hua Meng, Jun Yao, Bao-jie Wang School of Forensic Medicine, China Medical University, Shenyang 110122, People’s Republic of ChinaCorrespondence: Bao-jie WangSchool of Forensic Medicine, China Medical University, No. 77 Puhe Road, Shenbei New District, Shenyang 110122, People’s Republic of ChinaTel +8618842462979Email wangbaojie777@163.comPurpose: Abnormal expression of the NR1 subunit of the N-methyl-d-aspartate (NMDA) receptor may potentially increase the susceptibility to neuropsychiatric diseases. The purpose of this study was to investigate the functional sequence of the 3ʹUTR of the human GRIN1 gene, which encodes the GluN1 receptor to determine the effect on the expression of GluN1 receptor.Methods: We transferred seven recombinant pmirGLO recombinant vectors containing the 3ʹUTR truncated fragment of the GRIN1 gene into HEK-293, SK-N-SH, and U87 cell lines and compared the relative fluorescence intensity of adjacent length fragments. The TargetScan database was used to predict miRNAs. Then, miRNA mimics/inhibitors were co-transfected into the three cell lines with the 3ʹUTR of GRIN1 (pmirGLO - GRIN1), to investigate their influence on GRIN1 gene expression.Results: Compared with the pmirGLo-Basic vector, the relative fluorescence intensity of the complete GRIN1 gene 3ʹUTR recombinant sequence − 27 bp – +1284 bp (the next base of the stop codon is +1) was significantly decreased in all three cell lines. The relative fluorescence intensities were significantly different between − 27 bp – +294 bp and − 27 bp – +497 bp regions, and between − 27 bp – +708 bp and − 27 bp – +907 bp regions. According to the prediction of the TargetScan database and analysis, miR-212-5p, miR-324-3p and miR-326 may bind to +295 bp – +497 bp, while miR-491-5p may bind to +798 bp – +907 bp. After co-transfection of miRNA mimic/inhibitor or mimic/inhibitor NC with a recombinant vector in the 3ʹUTR region of GRIN1 gene, we found that has-miR-491-5p inhibited GRIN1 expression significantly in all three cell lines, while has-miR-326 inhibitor upregulated GRIN1 expression in HEK-293 and U87 cells.Conclusion: miR-491-5p may bind to the 3ʹUTR of the GRIN1 gene (+799 bp – +805 bp, the next base of the stop codon is +1) and down-regulate gene expression in HEK-293, SK-N-SH, and U87 cell lines, which implicates a potential role of miR-491-5p in central nervous system diseases.Keywords: human GRIN1 gene, 3ʹUTR, miRNA, GluN1 receptor, Parkinson’s disease